2021
DOI: 10.3889/oamjms.2021.7565
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Antimicrobial Nanoparticles on Flexural Strength and Hardness of Polymethylmethacrylate

Abstract: BACKGROUND: Polymethylmethacrylate (PMMA) is commonly used for dental appliances but has several shortcomings that could benefit from improvement with the use of nanoparticles (NPs). AIM: The purpose of this study was to modify PMMA with three different antimicrobial NPs; Graphene oxide nanosheets (nGO), Titanium dioxide NPs (TiO2 NPs) and curcumin (CUR)-loaded graphene oxide nanosheets alone, and in combination and assess the flexural strength and hardness of the different groups. MATERIALS AND METHODS: The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Antimicrobial graphene oxide nanosheets (nGO), TiO 2 nanoparticles (∼15 nm), and crystalline Curcumin (CUR) loaded nGO have been utilized as fillers of PMMA to study the flexural strength and hardness of the composites [13]. Among those fillers, they reported that TiO 2 nanoparticles are the most effective filler in improving flexural strength from 24.94 ± 5.37 MPa to 52.26 ± 5.48 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial graphene oxide nanosheets (nGO), TiO 2 nanoparticles (∼15 nm), and crystalline Curcumin (CUR) loaded nGO have been utilized as fillers of PMMA to study the flexural strength and hardness of the composites [13]. Among those fillers, they reported that TiO 2 nanoparticles are the most effective filler in improving flexural strength from 24.94 ± 5.37 MPa to 52.26 ± 5.48 MPa.…”
Section: Introductionmentioning
confidence: 99%